Artroskopicky asistovaná osteosyntéza nitrokloubních zlomenin lopatky – první zkušenosti a dvouleté klinické výsledky - Madeja, R; JeČmÍnek, V; Bialy, L; StrÁnskÝ, J; Voves, J; Pleva, L (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2020)
PURPOSE OF THE STUDY Fractures of the scapula are less frequent, with the incidence reported in literature of approximately 1% of all fractures and 3-5% fractures of shoulder. These fractures are predominantly treated non-operatively. Osteosynthesis is indicated in displaced intra-articular fractures and severely displaced extra-articular fractures of the scapular body, its lateral border in particular. Apart from open reposition and osteosynthesis, also minimally invasive osteosynthesis under fluoroscopic and arthroscopic control has recently been used to treat intra-articular fractures of the scapula. The arthroscopy facilitates debridement of the fracture line in the intra-articular region and control over the insertion of the osteosynthesis material in the subchondral bone of the glenoid and it also makes visible the accuracy of reduction of fractures of the glenoid articular surface. MATERIAL AND METHODS In 2013-2017, osteosyntheses of 9 intra-articular fractures of the scapula were performed with the use of both perioperative fluoroscopy and arthroscopy. The group included 7 men and 2 women, with the mean age of 37 years (range 24-52 years). 4.5 mm cannulated screws inserted in the subchondral bone either from the cranial or dorso-caudal part of the glenoid in dependence on the type of the fracture were used as osteosynthesis material. Postoperatively, the extremity was fixed by Desault type shoulder brace for 4 weeks. Rehabilitation using standard procedures for shoulder joint followed. The patients were followed up at regular intervals, namely on 10th day, at 4 weeks, 3, 6, 12 and 24 months postoperatively. The clinical outcomes and radiologic signs of healing were evaluated continuously and two years after the surgery the clinical outcomes were assessed using the Constant score. Arm elevation was assessed separately, as a dominant indicator of shoulder joint function. RESULTS No perioperative complications were reported, the operative times ranged from 45 to 120 minutes. Reduction was always performed in fractures with intra-articular displacement of less than 2 mm, which was measured both arthroscopically and on perioperative and postoperative radiographs. No complications of wound healing were observed. One patient experienced temporary paresthesia in the innervation zone of the sensitive branch of the radial nerve. The mean healing time of fractures was 121 days (range 107-146 days). The mean Constant score at two years after surgery was 83 points (range 78-87 points), the resulting restriction of elevation was 12° on average (range 0-23°). DISCUSSION There are not many papers covering a similar topic in world literature, most of them present the benefits of arthroscopy in some types of osteosyntheses of intra-articular fractures of the scapula. Most frequently mentioned are osteosyntheses of the anterior portion of the glenoid in case of a bony Bankart lesion. These papers highlight the benefits of minimal invasiveness of this procedure. CONCLUSIONS By visualising the fracture line, the arthroscopy facilitates a more accurate reduction of fragments and a minimally invasive osteosynthesis of some intra-articular fractures of the scapula when compared to closed reduction with fluoroscopic intraoperative control only. The use of arthroscopy in these interventions is conditional on perfect mastering of the surgical technique and also the use of special instruments both for arthroscopy and minimally invasive osteosynthesis. If these criteria are observed and the surgical technique mastered, the authors consider this method beneficial in treating the glenoid fractures. Key words: minimally invasive osteosynthesis, glenoid fractures.
Keywords: výsledek terapie; Young Adult; Male; Fracture Fixation, Internal; Scapula; mladý dospělý; vnitřní fixace fraktury; lopatka; Adult; dospělí; mužské pohlaví; fraktury proximálního humeru; artroskopie; Arthroscopy; Intra-Articular Fractures; Treatment Outcome; Shoulder Fractures; lidé; ženské pohlaví; Humans; Female; lidé středního věku; intraartikulární fraktury; Middle Aged